PEDAGOGICAL HARMONY AND DYNAMICS OF APPLICATION OF FORMS, METHODS, AND MEANS OF TEACHING STUDENTS - Zahorodnia, Tetiana; Chumak, Mykola (Mountain School of Ukrainian Carpaty, 2023)
Actual research of teachers and scientists of different countries in the field of pedagogical harmony has been analyzed, the issues of interaction between the teacher and the student, the formation of positive relationships in the classroom, special aspects of creating a favorable learning environment have been considered. Pedagogical support for the preparation of the future specialist engaged in pedagogical activities for harmonious interaction with the student has been theoretically substantiated and implemented. The issue of dynamics of modification of methods, forms, means of training, which help to create satisfaction with the educational process for both the student and the teacher, has been considered. Definitions and conditions of pedagogical harmony have been formulated, which consist in aligning the organization of education and target settings, comparing the content, forms, methods of teaching, transforming them into expressive means of the pedagogical process, which are aimed at creating satisfaction of students from a sense of harmony in the learning process and cognition of the surrounding world. It is proposed to assess the degree of harmony of the educational process one of the following levels: high, medium and low. The classification and requirements for the levels of harmoniousness of the educational process are given. Some types of learning motives and subgroups of methods used to form these motives are considered. It is shown that knowledge of forms and methods of teaching, pedagogical intuition and pedagogical tact of the teacher help to create a harmonious educational situation. The solution of the problem of determining the correspondence of the formed level of knowledge of the student, the applied forms, methods, means of teaching and the achieved level of harmony of the pedagogical process is proposed. The types of lessons are considered and the dynamics of the use of certain forms, methods and means of education, the use of which in its selection generates pedagogical harmony, are traced.